Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Pada PT. Mitra Megah Profitamas Banjarmasin - Zulvan Marinda Marzuki Siswanto; Fitriani Fitriani; Rini Amelia (P3M Politeknik Negeri Banjarmasin, 2022)
The purpose of this study is to find out what forms of Reward and Punishment are applied, as well as the effect of Reward and Punishment on Employee Performance at PT. Mirta Megah Profitamas Banjarmasin. The methodology in this research is descriptive quantitative. The population in this study were 122 employees at PT. Mitra Megah Profitamas Banjarmasin. The sampling technique was carried out using the Slovin formula. Based on these techniques, respondents were obtained by 93 employees. The data collection technique used was a questionnaire, the data collected was analyzed using descriptive analysis and multiple regression analysis. Research testing and analysis shows that Reward has a positive and significant effect on Employee Performance, then Punishment also has a positive and significant effect on Employee Performance. then simultaneously shows that Reward and Punishment have a positive and significant effect on employee performance.